Real-time monitoring of volume flow, mass flow and shredder power consumption in mixed solid waste processing. (15th July 2021) - Curtis, A.; Sarc, R.
Highlights: Conversion of volume flow to mass flow data with density determination is possible. Strong correlation between volume flow data and shredder power consumption data. Automatically measured volume and mass flow data result in fluctuating bulk densities. Strong correlation between volume flow data and mass flow data. Strong correlation between the proportion of certain fractions and the bulk density. Abstract: Real-time material flow monitoring is not yet implemented in mixed solid waste processing, but it is important for an efficient quality assured production and the development of the smart waste factory. The present paper shows results of practical investigation of the Real-Time Material Flow Monitoring in a large-scale Solid Recovered Fuel (SRF) production plant and a semi large-scale processing line (Technical line 4.0) using mixed solid waste. The investigations aimed to research the fundamentals for generating mass flow data from volume flow data and volume and mass flow data from shredder power consumption. It could be shown that a mass determination from volume flow data with the help of density determinations can be practically realized in a good approximation (deviation < 1%) to the gravimetrically determined mass in an SRF production plant. With R 2 = 0.47, the power consumption of a shredder in the SRF plant shows a low to medium correlation to the corresponding volume flow. In the 31 tests with the Technical Line 4.0, both, the mass flow and the volume flow could be measured in real-time. Combining these data results in the temporal density curve and shows strong fluctuations for shredded commercial waste. Comparing the mean bulk densities for each test with those from the density determinations of taken samples shows a robust correlation (R 2 = 0.82). Analyzes of the material composition of the shredded mixed solid waste show strong correlations to bulk density for the proportions of the fractions rest (positive correlation) and plastics (negative correlation).